Articular Gap and Step-off Revisited: 3D Quantification of Operative Reduction for Posterior Malleolar Fragments. Issue 12 (December 2016) - de Muinck Keizer, Robert-Jan O.; Meijer, Diederik T.; van der Gronde, Bonheur A. T. D.; Teunis, Teun; Stufkens, Sjoerd A. S.; Kerkhoffs, Gino M.; Goslings, J. Carel; Doornberg, Job N.
Abstract : Objectives: Despite advanced imaging techniques, classic measurements of fracture reduction have not been revisited to date. The purpose of this study was to evaluate the reliability of innovative measurement techniques to quantify operative fragment reduction of posterior malleolar fractures by quantification of three-dimensional computed tomography (Q3DCT). Methods: Twenty-eight ankle fractures including a posterior malleolar fragment (AO/OTA type 44) were evaluated using 2DCT and Q3DCT to postoperatively quantify fragment reduction. "Classic" maximum gap and step-off of the posterior fragment were measured on 2DCT and Q3DCT. In addition, 2 innovative Q3DCT parameters were introduced and their reliability was tested using intraclass correlations (ICCs): gap surface (mm 2 ) and multidirectional 3D-displacement (mm). Results: "Classic" measurements showed a median maximum step-off of 1.1 mm [interquartile range (IQR) 0.0–1.8 mm] on 2DCT versus a median step-off of 0.6 mm (IQR 0.0–1.1) on Q3DCT. Median maximum gap was 1.2 mm (IQR 0.0–3.8) on 2DCT, and its equivalent on Q3DCT showed no median displacement. Q3DCT measurements revealed a median gap surface of 14.5 mm 2 (IQR 4.7–30.0) and a median multidirectional 3D-displacement of 0.7 mm (IQR 0.0–1.1). Interrater reliability of these new Q3DCT parameters of displacement was excellent (ICC 0.92, 95% CI 0.79–0.98) for gap surface and good (ICC 0.64, 95% CI 0.28–0.88) for 3D-displacement. Conclusions: Q3DCT is a reliable and promising technique for postoperative evaluation of fracture fragment reduction. In addition to "classic" gap and step-off measurements, we propose to explore total gap surface and 3D-displacement as innovative radiographic measurements in future clinical studies. Level of Evidence: Diagnostic Level IV. See Instructions for Authors for a complete description of levels of evidence.